THE DEVELOPMENT OF INTERNATIONAL INTERNET TRADE IN THE MINDS OF THE BUSINESS CENTER - Chernukha, Tetiana (Social Economics, 2024)
The formation of key trajectories of the development of the global economy is closely related to the expansion of the use of modern information and communication technologies. An indicative aspect of this development trajectory is the establishment of trade relations with the help of Internet trade tools, which is a very promising direction of modern business operations on the Internet. It has been established that the increased use and integration of information and communication technologies (ICT) have far-reaching consequences, indirectly affecting various types of economic activity, especially those related to ICT-related industries. The organization of trade with the help of Internet technologies acts as a catalyst and stimulus for economic growth, opening a new qualitative stage of development. Close monitoring of the evolution of international Internet trade made it possible to comprehensively characterize the nature of its development, identify trends, and outline both promising milestones and potential threats in the complex web of international economic relations. Thus, a thorough study of trends and an assessment of the prospects of international Internet trade remains an urgent task in modern conditions. This search makes a significant contribution to understanding the nuances of dynamics, provides insight into the trajectory of international economic interactions, and promotes an active approach to solving new challenges facing the world. The purpose of the article is a critical study and analysis of the role of international Internet trade as a modern alternative to traditional methods of selling goods. The article examines the key features and mechanisms of international Internet trade, highlights its advantages and challenges in comparison with classical approaches to sales. The impact of technological progress, digital platforms and e-commerce trends on the evolution of international trade and consumer behavior is assessed. The potential consequences and future prospects of international Internet trade are identified, taking into account both the opportunities and risks for businesses operating in the global digital market.